Prevalence and associated factors of dyslipidemia among adults with coexisting chronic disease in Ethiopia: A systematic review and meta-analysis. - Tadesse Mekonen Zeleke; Fitsum Endale Liben; Tinsae Shemelise Tesfaye; Abiyu Legesse Munea; Fekede Asefa Kumsa (PLoS ONE)
Introduction Dyslipidemia is a well-established, modifiable risk factor for cardiovascular disease. This study aimed to determine the pooled prevalence of dyslipidemia, its components, and associated factors among adult patients residing in Ethiopia. Method A comprehensive search of articles was conducted using MEDLINE, Embase, African Journals Online, Google Scholar, and University repositories. The quality of the studies was evaluated using the Joanna Briggs Institute quality appraisal criteria. Dyslipidemia was defined based on the National Cholesterol Education Program Adult Treatment Panel III cut-off points. We pooled the effect sizes using a random-effects model in Stata (v.16). Subgroup and sensitivity analysis were also performed. Small study effect was assessed by Luis Furuya-Kanamori asymmetry index, Doi plot, funnel plot, and Egger's tests. Results Out of 640 initially identified articles, 104 underwent full-text review, and 62 met the inclusion criteria for the final analysis. The pooled prevalence of overall dyslipidemia was 64% (95% CI: 54-74%; I2 = 98.74; P < 0.001). The prevalence of elevated total cholesterol was 32% (95% CI: 27-36%; I2 = 97.09; P < 0.001), elevated total triglycerides was 43% (95% CI: 38-47%; I2 = 97.56; P < 0.001), elevated low-density lipoprotein was 30% (95% CI: 24-36%; I2 = 97.24; P < 0.001), and low high-density lipoprotein was 48% (95% CI: 42-54%; I2 = 98.53; P < 0.001). Having high wrist circumference, older age, being overweight or obese, residing in urban, being an alcohol consumer, being a smoker, and being physically inactive were associated with increased odds of dyslipidemia. Conclusion Dyslipidemia prevalence is alarmingly high among adults with coexisting chronic diseases in Ethiopia, posing a significant public health challenge. Regular screening, early detection, and prompt management of dyslipidemia are critical to addressing this issue.